NGHIÊN CỨU ỨNG DỤNG VI KHUẨN ĐỂ CẢI THIỆN CHẤT LƯỢNG ĐẤT CANH TÁC NÔNG NGHIỆP - Nguyễn, Thị Mỹ Lệ; Lê, Việt Hoàng; Nguyễn, Duy Tới; Đinh, Mai Vân; Đinh, Thuý Hằng; Nguyễn, Thị Hải (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
APPLICATION OF BENEFICIAL BACTERIA TO IMPROVE AGRICULTURAL SOIL QUALITYTwo bacterial strains, VK7 and SDT2.3, possess multiple biological activities beneficial to plants, including IAA production, siderophore synthesis, nitrogen fixation, EPS production, and phosphate solubilization. These strains are expected to have potential applications for improving agricultural soil quality. Based on comparisons of 16S rDNA sequences and rpoB gene sequences, these bacterial strains were identified as Bacillus velezensis VK7 and Ensifer sesbaniae SDT2.3.A bioformulation containing live cells of two strains VK7 and SDT2.3 was tested on degraded soil from a tea-cultivated farm with tomato plants under greenhouse conditions. After one crop season (4 months), soil properties improved significantly: total organic carbon increased by 16.51% and sand content in the soil mechanical composition rose by 120.11%. Enhanced soil quality was further evidenced by a 15.70% increase in green biomass (stem and leaf weight) compared to untreated control. Notably, the combined application of both bacterial strains reduced NPK fertilizer usage by 10% compared to conventional methods, with no adverse effects on plant growth or yield.